Company perceptions and responses to multi-level Arctic institutional environment and its reflection on their ECSR implementation practices : A comparative case study of two expedition cruise operators - Liimatainen, Sini (2024)
The Arctic region is warming rapidly, affecting the global climate and increasing commercial activities such as Arctic cruise tourism, which raises environmental concerns. The Arctic region has a multi-level institutional environment and similarly cruise ships are subject to different institutional arrangements. ECSR practices of companies are important in addressing environmental concerns and institutional pressures are linked to them. The study aims to explore how companies perceive and respond to the multi-level Arctic institutional environment and how it is reflected in their ECSR implementation practices. The theoretical framework of the study is built on existing literature related to ECSR, ECSR implementation, institutional theory, formal and informal institutions, and institutional pressures and company responses. The study uses a qualitative comparative case study method with a deductive approach to theory development. The empirical part of the study focuses on two Arctic expedition cruise operators and a multimethod approach is applied using semi-structured interviews and secondary data. The data is analysed through a thematic analysis. The findings suggest that the Arctic institutional environment is multi-level. The case companies perceive to be facing various institutional pressures when operating in the Arctic, respond to them with a combination of confirmatory and opportunity-seeking strategies, and these pressures and responses are reflected in their ECSR implementation practices in many ways. Both formal and informal external institutional pressures were identified and the informal pressures, coming especially from the local communities, were emphasized. Although the study focuses mostly on the external institutional pressures and drivers of ECSR, the importance of the internal pressures was also brought up by the interviewees. The case companies comply with the mandatory regulations, adapt to informal pressures as well as engage in other voluntary actions guided by internal pressures. The case ...